The Changing Nature of Manufacturing in OECD Economies - Pilat, Dirk (OECD Publishing, 2006)
This paper provides empirical evidence on the changing nature of manufacturing in OECD countries, including the continued loss of employment in the manufacturing. It examines the extent to which manufacturing output and employment are declining in OECD countries and explores possible causes, including increased productivity, slow growth in demand for manufacturing products, loss of markets to imports, statistical and classification issues, and so on. The paper finds that the share of manufacturing in OECD economies is declining and argues that this is likely to continue. It also presents...
Keywords: Science and Technology